Is Financial Fair Play really justified? An economic and legal assessment of UEFA's Financial Fair Play rules - Henning Vöpel (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2013)
There is an ongoing debate on how Financial Fair Play (FFP) will affect European club football and whether it is really fair. So far regulations have been very different among national leagues. Therefore, FFP is expected to trigger some asymmetric adjustments among clubs and leagues thereby leading to some changes in the competitive balance and probably to a new competitive equilibrium in European club football in an inter- as well as in an intra-league comparison. The Paper discusses to what regard and to what extent FFP rules are really needed to remedy market failure and whether these rules are legitimate or justifiable with respect to their objectives and potential conflicts with EU competition law.
Keywords: 330